2015
DOI: 10.1186/s40303-015-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of agomelatine-induced liver injury

Abstract: Agomelatine is an antidepressant with a unique mechanism of action. Since its marketing in 2009, concerns have been raised regarding its potential to induce liver injury. The authors therefore address the need to comprehensively evaluate the potential risk posed by agomelatine of inducing liver injury by reviewing data from published and unpublished clinical trials in both the pre- and postmarketing settings, as well as data from non-interventional studies, pharmacovigilance database reviews and one case repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 43 publications
1
27
1
2
Order By: Relevance
“…Agomelatine (based on our small cumulative samples) was the only drug with established effectiveness among the new pharmacologic options to treat GAD, and showed improved acceptability compared to active drugs including benzodiazepine, quetiapine and paroxetine. In practice however, agomelatine may have limited use on account of concerns about liver toxicity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Agomelatine (based on our small cumulative samples) was the only drug with established effectiveness among the new pharmacologic options to treat GAD, and showed improved acceptability compared to active drugs including benzodiazepine, quetiapine and paroxetine. In practice however, agomelatine may have limited use on account of concerns about liver toxicity [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the risk of liver toxicity for nefazodone was so high that it was subsequently withdrawn from the market [45]. A recent systematic review found that the incidence of agomelatine-induced liver injury was as high as 4.6% and the risk of liver injury appeared to be dose dependent [46]. Case reports of life-threatening liver toxicity, in some cases requiring liver transplantation, have been described in the literature for nefazodone, duloxetine, venlafaxine and agomelatine [41].…”
Section: Hepatotoxicity and Hypersensitivity Reactionsmentioning
confidence: 99%
“…agomelatine, and duloxetine [30]. In a systematic review of agomelatine-induced liver injuries [31], agomelatine was found to be associated with higher rates of liver injury than a placebo, escitalopram, paroxetine, fluoxetine, and sertraline, and a positive relationship was evidenced between agomelatine dose and liver injury. In a recent study of 896 patients with depression using agomelatine [32], liver enzymes (AST, ALT, GGT, ALP) were found to be elevated after 12 weeks of treatment, although these elevations did not exceed three times the upper limits of the established norms.…”
Section: Metabolic Parametersmentioning
confidence: 99%